y=(x-r1)(x-r2) +b
= (x-2-sqrt3)(x-2+sqrt3)+b
= (x^2 -1) + b
for the point 2,5
5=(4-1)+b
solve for b, and you have it.
Determine the equation of the parabola with roots 2+sqrt(3) and 2-sqrt(3), and passing through the point (2,5).
7 answers
I respectfully must disagree with Bob
Since we know the roots, we can say the equation is
y = a(x-2-sqrt(3))(x-2+sqrt(3))
y = a(x^2 - 4x + 1)
plug in (2,5)
5 = a(4-8+1)
a= -5/3
equation: y = (-5/3)(x^2 - 4x + 1)
or y = (-5/3)(x-2)^2 + 5 after completing the square.
check:
#1: solving (-5/3)(x-2)^2 + 5 yiels 2 ± sqrt(3) , and
#2: (2,5) satisfies the equation.
Since we know the roots, we can say the equation is
y = a(x-2-sqrt(3))(x-2+sqrt(3))
y = a(x^2 - 4x + 1)
plug in (2,5)
5 = a(4-8+1)
a= -5/3
equation: y = (-5/3)(x^2 - 4x + 1)
or y = (-5/3)(x-2)^2 + 5 after completing the square.
check:
#1: solving (-5/3)(x-2)^2 + 5 yiels 2 ± sqrt(3) , and
#2: (2,5) satisfies the equation.
Reiny is correct. I did it in my head, and missed the second term. Ugh.
Given: Ints 2 + sqrt(3) , 2 - sqrt(3).
x = 2 + sqrt(3),
x - 2 = sqrt(3),
Square both sides:
x^2 - 4x + 4 = 3,
Set Eq = 0:
x^2 - 4x + 1 = 0,
EQ: Y = X^2 - 4X + 1.
h = Xv = -a/b =4/2 = 2,
K = Yv = 2^2 - 4*2 + 1 - -3
V(2 , -3).
CHECK: y = (2 - sqrt(3)^2 -4(2 - sqrt(3)) + 1,
y = 4 - 4*sqrt(3) + 3 -8 + 4*sqrt(3)
+ 1,
Combine like-terms:
4 + 3 - 8 + 1 = 0. Ints satisfies EQ.
The X-Ints nd vertex satisfy the Eq, but the given point do not. Please
check the point for error.
x = 2 + sqrt(3),
x - 2 = sqrt(3),
Square both sides:
x^2 - 4x + 4 = 3,
Set Eq = 0:
x^2 - 4x + 1 = 0,
EQ: Y = X^2 - 4X + 1.
h = Xv = -a/b =4/2 = 2,
K = Yv = 2^2 - 4*2 + 1 - -3
V(2 , -3).
CHECK: y = (2 - sqrt(3)^2 -4(2 - sqrt(3)) + 1,
y = 4 - 4*sqrt(3) + 3 -8 + 4*sqrt(3)
+ 1,
Combine like-terms:
4 + 3 - 8 + 1 = 0. Ints satisfies EQ.
The X-Ints nd vertex satisfy the Eq, but the given point do not. Please
check the point for error.
Thank you!
Henry, the point (2,5) does not satisfy your equation.
The point (2,5) is the vertex, not (2,-3)
The point (2,5) is the vertex, not (2,-3)
y=a(x - 2 - sqrt(3))(x - 2 + sqrt(3))
FOIL = First Outsisde Inside Last
y=a(x^2 - 2x + 1x - 2x + 4 - 2sqrt(3) - 1x + 2sqrt(3) - sqrt(9))
y=a(x^2 - 2x + 1x - 2x - 1x + 4 - 3("Is the sqrt(9)") - 2sqrt(3) + 2sqrt(3))
y=a(x^2 - 4x + 1)
Plug in points
5=a(2^2 - 4(2) + 1)
5=a(4 - 8 + 1)
5=a(3)
a=-5/3
Plug that our equation (x^2 - 4x + 1)
y=(-5/3^2 - 4/1(-5/3) + 1(-5/3))
y=25/9 - 20/3 - 5/3
ANSWER:
y=5/3 - 20/3 - 5/3
FOIL = First Outsisde Inside Last
y=a(x^2 - 2x + 1x - 2x + 4 - 2sqrt(3) - 1x + 2sqrt(3) - sqrt(9))
y=a(x^2 - 2x + 1x - 2x - 1x + 4 - 3("Is the sqrt(9)") - 2sqrt(3) + 2sqrt(3))
y=a(x^2 - 4x + 1)
Plug in points
5=a(2^2 - 4(2) + 1)
5=a(4 - 8 + 1)
5=a(3)
a=-5/3
Plug that our equation (x^2 - 4x + 1)
y=(-5/3^2 - 4/1(-5/3) + 1(-5/3))
y=25/9 - 20/3 - 5/3
ANSWER:
y=5/3 - 20/3 - 5/3